2015
DOI: 10.1155/2015/357360
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect of Leptin on Liver Damage in Case of Hepatic Injury Associated with Paracetamol Poisoning

Abstract: Background Aim. In case of high-dose acetaminophen intake, the active metabolite can not bind to the glutathione, thereby inducing cellular necrosis through binding to the cytosol proteins. This trial was performed to histologically and biochemically investigate whether leptin was protective against liver damage induced by paracetamol at toxic doses. Material and Method. In our trial, 30 female rats, divided into 5 groups, were used. IP leptin administration was performed after an hour in the group of rats, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Besides alcohol, other drugs and medical treatments can also damage the liver by an alteration in leptin secretion, causing changes in lipid homeostasis that could lead to fatty liver disease, steatohepatitis and even cirrhosis [ 226 , 227 ]. Promising results, obtained in animal models, support that leptin can provide protection against the lipid peroxidation characteristic of paracetamol-associated liver damage [ 228 ], probably because leptin has a direct effect on cytochrome P-450 protein family, conjugation and antioxidant enzymes that play an essential role in detoxification processes in liver microsomes [ 229 ]. The impact of leptin signaling in the participation of liver cytochrome metabolism has also been demonstrated by Larson et al These authors have shown that cytochrome P450 1b1 (Cyp1b1), that has an important role in the oxidative metabolism of xenobiotics, likewise plays a key function in the modulation of liver fatty acid homeostasis.…”
Section: Leptin and Other Liver Pathologiesmentioning
confidence: 99%
“…Besides alcohol, other drugs and medical treatments can also damage the liver by an alteration in leptin secretion, causing changes in lipid homeostasis that could lead to fatty liver disease, steatohepatitis and even cirrhosis [ 226 , 227 ]. Promising results, obtained in animal models, support that leptin can provide protection against the lipid peroxidation characteristic of paracetamol-associated liver damage [ 228 ], probably because leptin has a direct effect on cytochrome P-450 protein family, conjugation and antioxidant enzymes that play an essential role in detoxification processes in liver microsomes [ 229 ]. The impact of leptin signaling in the participation of liver cytochrome metabolism has also been demonstrated by Larson et al These authors have shown that cytochrome P450 1b1 (Cyp1b1), that has an important role in the oxidative metabolism of xenobiotics, likewise plays a key function in the modulation of liver fatty acid homeostasis.…”
Section: Leptin and Other Liver Pathologiesmentioning
confidence: 99%
“…These changes could be due to increased NAPQI production and lipid peroxidation as a result of mitochondrial GSH depletion by NAPQI conjugation which lead to cytochrom P450 bioactivation especially in the centrilobular cells by Oz et al 18 and Galal et al 19 . Moreover the increased oxidative stress leads to release of more proinflammatory cytokines particularly TNF-alpha that leads o apoptotic damage by Murat et al 20 .…”
Section: Histogram: 1 Discussionmentioning
confidence: 99%
“…Such elevation of intermediate peroxidation products correlated with the level of antioxidant system inhibition, i.e. with the reduced level of glutathione and enzymes participating in its metabolism, and the level of superoxide dismutase and catalase [ 55 ]. Similarly, lipid peroxide in the liver or blood serum of the animals is observed in case of the long-term introduction of lower doses of paracetamol (100 and 250 mg/kg b.w.)…”
Section: In Vivo Modelsmentioning
confidence: 99%